2021
DOI: 10.7150/ijbs.54014
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of miR-619-5p in resistance to cisplatin by regulating ATXN3 in oral squamous cell carcinoma

Abstract: MicroRNAs are major post-transcriptional regulators responsible for the development of human cancers, including OSCC. The specific role of miR-619-5p in OSCC, however, is rarely reported. Cisplatin is one of the mostly applied chemotherapy drugs of OSCC. Nevertheless, drug resistance of cisplatin following the initial chemotherapy largely restricts its clinical benefits, and the mechanism of cisplatin resistance is unclear. This study intends to explore the biological function of miR-619-5p in the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The miR-619-5p/ATXN3 axis provided the potential molecular mechanism of OSCC, especially for promoting drug resistance of cisplatin of OSCC. And ATXN3 may be a putative therapeutic target for OSCC patients (Song et al, 2021). In addition, ATXN3 knockdown can inhibit cell growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The miR-619-5p/ATXN3 axis provided the potential molecular mechanism of OSCC, especially for promoting drug resistance of cisplatin of OSCC. And ATXN3 may be a putative therapeutic target for OSCC patients (Song et al, 2021). In addition, ATXN3 knockdown can inhibit cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that oral squamous cell carcinoma (OSCC) (Song et al, 2021), testicular cancer (TC) (Shi et al, 2018), colon cancer (Li et al, 2019), breast cancer (BC) (Zou et al, 2019), anaplastic thyroid carcinoma (ATC) (Zhuang et al, 2021), neuroblastoma (NB) (Gong et al, 2021), non-small cell lung cancer (NSCLC) (Sacco et al, 2014), and breast cancer stem cells (Zhu et al, 2019)were closely related to ATXN3. For example, for oral squamous cell carcinoma, it had been studied that down-regulated miR-619-5p promoted the proliferation, migration, and invasion abilities by enhancing ATXN3 expression in OSCC cisplatin-resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal-associated invariant T (MAIT) cells and γδ T cells released inflammatory cytokines to respond to invasion [ 10 ]. Early response immune effector cells, including CTL and NK cells, were activated to fight the virus [ 11 ]. A number of studies have shown that the sign of COVID-19 was the cytokine storm with elevated levels of interleukin-6 (IL-6), IL-1 β , complement C1r (C1R), tumor necrosis factor-alpha (TNF- α ), chemokine (C-C-motif) ligand 2 (CCL2), and granulocyte-macrophage colony-stimulating factor (GM-CSF) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that miR-619-5p reduced OSCC cells migration via PI3K/AKT pathway. MiR-619-5p increased CDDP sensitivity in OSCC cells by ATXN3 targeting [ 190 ].…”
Section: Role Of Mirnas In Cddp Reponse In Hnc Cells By Regulation Of...mentioning
confidence: 99%